A28 Accumulation and aggregation of human mutant huntingtin and neuron atrophy in BAC-HD transgenic rat. (16th November 2010) - Yu, L; Metzger, S; Clemens, L E; Ehrismann, J; Ott, T; Gu, X; Gray, M; Yang, W; Osmand, A P; Riess, O; Nguyen, H P
Abstract : Background and aim: We have previously generated and characterised in detail transgenic rats which express a fragment of mutant huntingtin (htt). This rat model mirrors many aspects of Huntington's disease (HD) but it lacks the full length mutant htt protein and therefore some aspects of the human condition might be imperfectly replicated. In order to remedy this, we have generated BAC-HD transgenic rats expressing full length human mutant huntingtin. Methods: Bacterial artificial chromosomes (BACs) were used, which contained human genomic DNA spanning the full length gene with 97 CAG/CAA repeats including all regulatory elements. Two lines were selected for further phenotyping, one with the highest RNA and protein expression level and a second line with similar expression level as seen in BAC-HD mice. Outcomes: Primary characterisation already indicated an early progressive HD-like phenotype including progressive motor deficits, impaired motor skill learning and reduced activity. In this study, we demonstrate HD characteristic neuropathological changes such as aggregation of mhtt in BAC-HD rats. Large numbers of neuropil aggregates are seen in the bed nucleus of stria terminalis (BSRc) and in cortex as well as in the amygdala and hippocampus. Additionally, a huge amount of nuclear accumulation of mhtt is present in cortex in both lines of BAC-HD rats at 12 months of age. Furthermore, decreased staining of the medium spiny neuron marker DARPP32 was observed in the striatum. Conclusion: These two lines show robust neuropathological changes in addition to the early HD-like phenotype making them valuable for future preclinical therapy studies and better understanding of HD pathogenesis.